Performance of Gmelina arborea and Emblica officinalis under Agroforestry on Fallow Lands in Uttarakhand and Uttar Pradesh - Singh, Rambir; Srivastava, Anubha; Singh, Charan; Gulati, Ajay (Indian Forester, 2020)
The study is the outcome of performance of Gamhar (Gmelina arborea) and Aonla (Emblica officinalis) under agroforestry on fallow lands. Agroforestry models were established with G. arborea and grafted E. officinalis var. NA-7 planted in Randomized Block Design at 4m × 5m and 5m × 5m spacing with Rabi crops like Wheat-Barley and Kharif crops Groundnut-Paddy at the above sites. It was observed that the soil at Kodapur (Prayagraj) site is alkaline in nature with 8.30 pH in comparison of both sites at Dhaluwala majbata (7.12 pH) and Fatehpur Pelio (7.36 pH). Available Phosphorus was found in medium ranges at all sites. Available nitrogen and potassium were found in low ranges at Dhaluwala majbata than the sites at Fatehpur Pelio and Kodapur. Both species of G. arborea and E. officinalis performed well on these fallow lands. The growth parameter of G. arborea and E. officinalis showed a regular increase both in height and girth along with agriculture crops at all sites. The Initial Increment of both species G. arborea with height 189.45 cm and girth 18.15 cm in mixed planting at Dhaluwala with 5 × 5 m spacing and E. officinalis of height 74.67 cm in control plot at Fatehpur Pelio with 5 × 5 m spacing and girth 7.11 cm in control plot at Dhaluwala with 4 × 5 m spacing were found maximum in comparison to other sites after completion of one year plantation. The present study reflects, the initial growth of Gamhar (G. arborea) and grafted Aonla (E. officinalis) on fallow lands in Uttarakhand and Uttar Pradesh states are fast growing species and also short rotation suitable cash crops, which are capable to improve the livelihood of farmers.